2015
DOI: 10.1371/journal.pone.0116775
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation in Acute Exacerbation of Idiopathic Pulmonary Fibrosis

Abstract: BackgroundAcute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) is a common cause of disease acceleration in IPF and has a major impact on mortality. The role of macrophage activation in AE of IPF has never been addressed before.MethodsWe evaluated BAL cell cytokine profiles and BAL differential cell counts in 71 IPF patients w/wo AE and in 20 healthy volunteers. Twelve patients suffered from AE at initial diagnosis while sixteen patients developed AE in the 24 months of follow-up. The levels of IL-1r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 41 publications
15
133
0
1
Order By: Relevance
“…92 The presence of these alternatively activated macrophages has been linked to acute exacerbation of IPF patients consistent with the idea that macrophages can modulate the stability or progression of IPF. 95 When macrophages from the lungs of healthy controls or IPF patients were cultured and stimulated with collagen monomers, the IPFderived macrophages increased expression of profibrotic markers and cytokines, consistent with a classification of the alternative activated state. 96 Although macrophages can clearly promote fibrogenesis, depletion of macrophages during the recovery phase of both toxic liver injury and the lung bleomycin fibrosis models delayed the resolution of fibrosis.…”
Section: Role Of Inflammatory Cells In Lung Fibrosis Resolutionsupporting
confidence: 53%
“…92 The presence of these alternatively activated macrophages has been linked to acute exacerbation of IPF patients consistent with the idea that macrophages can modulate the stability or progression of IPF. 95 When macrophages from the lungs of healthy controls or IPF patients were cultured and stimulated with collagen monomers, the IPFderived macrophages increased expression of profibrotic markers and cytokines, consistent with a classification of the alternative activated state. 96 Although macrophages can clearly promote fibrogenesis, depletion of macrophages during the recovery phase of both toxic liver injury and the lung bleomycin fibrosis models delayed the resolution of fibrosis.…”
Section: Role Of Inflammatory Cells In Lung Fibrosis Resolutionsupporting
confidence: 53%
“…These diseases have in common to lead ultimately to formation of granulomas and a fibrotic phase (Girard et al, 2009;Facco et al, 2011). The mechanisms involved in IPF immunopathology remain poorly understood but include macrophage activation, fibrotic foci formation, possibly Th1 promoted (Schupp et al, 2015;Oruqaj et al, 2015). No Th2 switch was described for any of these ILD.…”
Section: Discussionmentioning
confidence: 99%
“…A panel of 10 key cytokines/chemokines were selected for testing, based on the scientific literature concerning ILD immunopathology (Mroz et al, 2008;Ye et al, 2009;Joshi et al, 2009;Simonian et al, 2009;Andrews et al, 2016;Tondell et al, 2014;Facco et al, 2011;Schupp et al, 2015;Oruqaj et al, 2015): IL-8, IL-6, TNFα, IFNγ, IL-1β (Th1 response), IL-4 (Th2 response) and IL-17, IL-21 and IL-23 (Th17 response). The TSLP, unexplored up to now, was also measured in patient's BALF (Kuethe et al, 2014).…”
Section: Luminex Immunoassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of LCAP is through the removal of activated leukocytes (13). Some investigators have observed activated leukocytes such as neutrophils and macrophages in patients with AE of IIPs (AE-IIPs) (3,14). Therefore, we hypothesized that LCAP may improve the general and respiratory condition of patients with AE-IIPs.…”
Section: Introductionmentioning
confidence: 99%